Epistemological approach to complex thought of phytopathological sciencie - Tirado-Lara, James (2025)
Introduction. The importance of scientific knowledge as a tool for reflection and for understanding philosophical evolution is not commonly considered. From the early belief in the spontaneous origin of plant diseases to the identification of their causal agents, this progression helps researchers recognize the relevance of epistemology within Plant Pathology. The epistemological perspective of phytopathology as a key element in society remains poorly understood, even though its evolution has contributed significantly to the advancement of scientific thought. The interaction among plants, pathogen, and environmental conditions represents a complex system that also involves society and exerts substantial impacts on both the economy and the environment. Objective. This study aims to analyze and demonstrate the inter- and multidisciplinary nature of scientific research or phytopathological epistemology within a global and social context. Methodology. Information sources related to phytopathological and philosophical sciences were identified using academic and scientific search engines. Relevant data were extracted from reliable scientific articles and other printed and digital publications. Analysis. The host, the phytopathogen, and the human being exchange matter with the surrounding environment, behaving as open systems. Phytopathogens cause host cell death, which in turn triggers plant defense mechanisms. Plant disease causes damage that affects society, leading to the implementation of management strategies which, in turn, stimulate innovation, creation, and evolution—processes that are intrinsic to the epistemology of phytopathological sciences. Conclusion. Phytopathological epistemology promotes the understanding of the complex pathogen–plant–environment–human system within a global framework that contributes to reducing social, political, and economic risks.